2019
DOI: 10.3390/su11092651
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Students’ Sustainability Awareness and the Curriculum of Technology Education in Pakistan

Abstract: Various fields of manufacturing, management, and business, including technology education, software development, and information communication technology (ICT), have espoused sustainability concepts. Including sustainability concepts in technology, education can help students learn how to implement the dimensions of sustainability (economic, social, and environmental). Lack of awareness and education regarding sustainability among students can impact their competence to incorporate sustainability into technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
0
35
0
6
Order By: Relevance
“…The list of existing studies that reported the challenge for the smart city development is described in Table 1. Growing technologies of ICT, IoT, and big data analytics are the basic infrastructure support (Malik et al, 2019), incorporating those utilised for smart city development, provides possible resolutions to these and other urbanisation challenges. It is a foundation for economic development and competitiveness (Lytras & Visvizi, 2018).…”
Section: Smart City Developmentmentioning
confidence: 99%
“…The list of existing studies that reported the challenge for the smart city development is described in Table 1. Growing technologies of ICT, IoT, and big data analytics are the basic infrastructure support (Malik et al, 2019), incorporating those utilised for smart city development, provides possible resolutions to these and other urbanisation challenges. It is a foundation for economic development and competitiveness (Lytras & Visvizi, 2018).…”
Section: Smart City Developmentmentioning
confidence: 99%
“…Indeed, the United Nations Global Compact has described business ethics and CSR courses as tremendously important in shaping the behavior of business professionals and leaders [6,7] and has repeatedly called on universities worldwide to help their students become active agents who work for a sustainable business and global economy [7]. Not surprisingly, HE has spent the last decade devoting significant resources to training in business ethics, sustainability and corporate social responsibility [8][9][10][11]-as a result, many business schools have implemented such courses in their educational curricula for undergraduate and postgraduate students [12]. By including a sustainability and CSR course that teaches key rules and processes (e.g., the golden rule, the silver rule, the platinum principle, the Rawls' veil of ignorance rule, the multi-stakeholders engagement rule, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the seventh target of this objective explicitly mentions the importance of ensuring that students acquire the theoretical and practical knowledge to promote sustainable development. Thus, Education for sustainability (EDS), from a formal [6][7][8][9][10][11][12][13], teaching training [14][15][16], and non-formal [17][18][19] perspective, is essential for Sustainability 2019, 11, 5182 2 of 14 instilling in students not only content and concepts, but also the fundamental values that make them sensitive in matters of sustainability.…”
Section: Introductionmentioning
confidence: 99%